2021
DOI: 10.1177/03009858211030542
|View full text |Cite
|
Sign up to set email alerts
|

Feline pyloric and duodenal adenoma: A histological and immunohistochemical study

Abstract: Although pyloric and duodenal adenomas occasionally occur in cats, limited information is currently available on their phenotypes and molecular features. The present study investigated the pathological features of these tumors and the mechanisms underlying their tumorigenesis. Biopsy samples from 8 cats diagnosed with pyloric or duodenal adenomas were examined by histopathology and immunohistochemistry. Normal pyloric and duodenal tissues of cats were assessed for comparison. All cases showed a papillary growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…In the literature, polyps were mostly described in the feline stomach or small intestine [6,40,41,61,62]. In contrast, in our study, polyps of the large intestine were found in 12 of 23 cases.…”
Section: Discussioncontrasting
confidence: 74%
“…In the literature, polyps were mostly described in the feline stomach or small intestine [6,40,41,61,62]. In contrast, in our study, polyps of the large intestine were found in 12 of 23 cases.…”
Section: Discussioncontrasting
confidence: 74%
“…In feline pyloroduodenal hyperplastic polyps, a differential for BG adenomas, the polyps arise from the surface epithelium, have a characteristic tubulopapillary arrangement of cells that retain surface mucous cell differentiation, do not invade underlying tissue and may contain abundant inflammatory cells (hyperplastic inflammatory polyps). 10 12 In gastric adenomas, benign surface epithelial cells lose mucous cell differentiation. 13 …”
Section: Discussionmentioning
confidence: 99%
“…The pyloric glands mainly secrete mucus and HCO3-, which together form a barrier against gastric mucosal injury, called mucus-bicarbonate barrier. It can effectively prevent gastric acid and pepsin damage to the stomach [28]. However, in the early stage of CAG, the atrophy range is limited, the number of pyloric glands is reduced, the secretion of mucus and HCO3-is reduced, and the mucus-bicarbonate barrier is thinned, but it will not affect the gastric parietal cells located in the gastric body and the bottom of the stomach (mainly secrete gastric acid).…”
Section: Mechanism Of Cuttlebone In the Treatment Of Cagmentioning
confidence: 99%